IMPROVEMENT OF PRODUCTIVITY ON EDUCATIONAL TOYS CRAFTSMEN THROUGH TRAINING OF PRODUCTION AND DIGITAL MARKETING - Wiwin Puspita Hadi; Lilis Suaibah (JCES (Journal of Character Education Society), 2021)
Abstrak: Media pembelajaran dapat digunakan untuk mencapai tujuan pembelajaran. Salah satunya adalah penggunaan media edukatif yang ramah lingkungan. Tujuan dari Program Kemitraan Masyarakat (PKM) ini adalah memberikan alternatif pemecahan masalah mitra dalam hal produksi, pemasaran, manajemen usaha dan implementasi dalam kegiatan pembelajaran untuk membuat alat permainan edukasi. Selama ini mitra menjalankan usaha kerajinan pembuatan truk mainan kayu sebagai produk utama dan mainan edukatif sebagai produk pelengkap. Metode pelaksanaan dalam kegiatan pengabdian ini meliputi analisis situasi dan perumusan masalah mitra, pelatihan produksi dan pelatihan e commerce untuk memperluas pemasaran. Hasil pengabdian adalah  peningkatan keterampilan dan pengetahuan mitra dalam hal produksi dan diversifikasi produk dan perluasan pemasaran yang diharapkan mampu meningkatkan kesejahteraan.Abstract: Learning objective achieves by learning media. One of them is the use of environmentally friendly educational media. The purpose of the Program Kemitraan Masyarakat (PKM) is to provide alternative solutions to partner problems in production, marketing, business management, and implementation in learning activities to make educational game tools. Partners have been running a craft business to manufacture wooden toy trucks as the main product and educational toys as a complementary product. This service activity's implementation method includes situation analysis and partner problem formulation, production training, and e-commerce training to expand marketing. The result of this service is an increase in the skills and knowledge production and product diversification and expansion of marketing which, are expected to increase welfare.